Re-engineering management: The role of visionary leadership and strategic planning in organizational education transformation - Hermawan, Rido; Anggraeni, RR Dewi; Yunus Amar, Muh; Rahman Kadir, Abdul; Hamid, Nurjannah (LPMPP Universitas Negeri Yogyakarta, 2025)
This paper explores the critical intersection of visionary leadership and strategic planning in the context of re-engineering management and organizational transformation. As businesses face rapid changes and increased competition, the need for effective transformation strategies has become paramount. Visionary leadership is identified as a crucial element that motivates and directs organizations through the complexities of change, fostering a shared vision that aligns with strategic goals. Additionally, strategic planning serves as a systematic approach that enables organizations to evaluate their current capabilities, define objectives, and outline actionable steps necessary for successful transformation. The synergy between these two components not only facilitates improved adaptability and innovation but also enhances overall organizational performance. This study emphasizes the importance of integrating visionary leadership and strategic planning as essential tools for navigating transformational challenges and achieving sustainable success in today’s dynamic business environment.